Elbashar Yahia H., Rayan D.A.,Saleh Hedra Emad R.and Rassoul Roshdy A. Abdel, Optical Spectroscopic Analysis of Neodymium Oxide Doped Phosphate Glass Matrix for Solar Energy Applications, Nonlinear Optics, Quantum Optics: Concepts in Modern Optics . 2021, - Nagendra, Chikkam Ajit Satya; Rajoriya, Jitendra Singh; Risheen, Daniel; Shrivastava, Snigdha; Reddy, Vedha Vyas (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present work was carried out on thirty Sahiwal cows selected from different villages in and around Rewa city of Madhya Pradesh. They were divided into 5 equal groups (n=6 each) to study the effect of clomiphene citrate, co-synch protocol and mineral supplementation alone or in combination on estrus induction, hormone concentration and fertility. Group 1, animals were fed ration containing 0% mineral mixture; Group 2, were fed ration containing clomiphene citrate (300 mg/ day for 5 days). In Group 3, the animals were subjected to co-synch protocol with fixed-time artificial insemination (FTAI) on day 11. Group 4 animals were fed ration containing a mineral mixture 1% and clomiphene citrate (300 mg/ day for 5 days). In Group 5, the animals were fed ration containing mineral mixture 1% and subjected to co-synch protocol. A significant difference was seen in progesterone concentration on day 42 and 60, while in estrogen, a significant difference was seen on day 9. Maximum conception rate (60%) was observed in animals that were supplemented with mineral mixture along with co-synch protocol (G5) followed by 50% with co-synch protocol alone (G3), and least conception rate (i.e., 0%) was observed in control group (G1). In group 4, mineral mixture supplementation with clomiphene citrate, no significant increase in fertility rate (33.33%) was noted. However, a higher estrus induction rate (50%) was observed, whereas in group 5 mineral mixture supplementation along with co-synch protocol increased the estrus induction (83.33%) and fertility rate (upto 60%) in anestrus Sahiwal cows.